The silver thread - Duey, Kathleen; Rayyan, Omar (New York : Aladdin Paperbacks, 2001)
When her beloved Moonsilver, the unicorn, is nearly killed by a hunter's arrow, Heart sneaks back into her village to get help from the healer, Ruth Oakes. Danger awaits and Heart must flee with Ruth's gift-a silver thread-to protect her and Moonsilver.
570L
Decoding demand: 79 (high) Semantic demand: 98 (very high) Syntactic demand: 79 (high) Structure demand: 87 (very high)
Accelerated Reader AR
Keywords: Foundlings -- Juvenile fiction; Unicorns -- Juvenile fiction